Ab initio molecular dynamics study on the disordered Li–Ga–Sn system. Issue 17 (21st April 2022) - Ding, An; Han, Bo; Zhang, Shiwei; Huang, Qi; Wang, Jianchuan; Wei, Chengyang; Du, Yong; Seifert, Hans J.
Abstract : AIMD simulations are performed to understand the structural, thermodynamic and thermophysical properties of disordered Li–Ga–Sn alloys formed in the initial stage of lithiation of liquid Ga91.6 Sn8.4 . Abstract : The eutectic Ga91.6 Sn8.4 liquid metal could serve as the anode in Li-ion batteries to avoid dendrite growth issue and volume expansion, and maintain a good cycle life. However, the microstructure and the basic physical properties of the lithiated Ga91.6 Sn8.4 are ignored in experiments and still unclear. In this work, we assume that a disordered structure is formed in the initial stage of lithiation of Ga91.6 Sn8.4, and the structure, equilibrium density, thermal expansion coefficient, mixing enthalpy, self-diffusion coefficient and viscosity of the disordered Li–Ga–Sn system are investigated systematically by ab initio molecular dynamics. The radial distribution function, structure factor and bond angle distribution function are calculated to obtain local structure information. Our calculations show that the lithiation of Ga91.6 Sn8.4 is exothermic, and for most cases, the diffusion coefficients for Li, Ga and Sn decrease with increasing Li content. Based on structural information and diffusion coefficients, we reveal that the lithiation of Ga91.6 Sn8.4 will make the liquid Ga91.6 Sn8.4 alloy form a solid-like structure. With the increase of Li content, it is more likely to form a solid-like structure. Furthermore, our simulations reveal that the chemical interaction of Li–Sn and Li–Ga is stronger than that of Ga–Sn, and Li is prone to combine with Sn firstly in the lithiation process of Ga91.6 Sn8.4 .